Modeling and forecasting volatility of index return: an empirical evidence of FTSE 100 Index - ZHU, Lin (2013)
Volatility forecasting in an important area of research in financial markets and immense effort expended in improving volatility models, since better forecasts will ultimately lead to more accurate options pricing and better risk management. This thesis attempts at modeling and forecasting the volatility of FTSE 100 index return of United Kingdom market, using daily and weekly frequency data range from January 1, 2003 to July 31, 2013. For each return series, the last 60 observations are used as holdout sample for out-of-sample forecast evaluation. The forecasting models that are considered in this study range from the relative simple GARCH (1, 1) model to relatively complex GARCH models, including Exponential GARCH (p, q), Threshold GARCH (p, q) and GJR-GARCH (p, q).